2007
DOI: 10.1080/19942060.2007.11015186
|View full text |Cite
|
Sign up to set email alerts
|

A Review of CFD Modelling for Performance Predictions of Hydrocyclone

Abstract: A critical assessment is presented for the existing numerical models used for the performance prediction of hydrocyclones. As the present discussion indicates, the flow inside a hydrocyclone is quite complex and there have been numerous numerical studies on the flows and the particle motions in hydrocyclone, with a wide range of turbulence and multiphase models tested. Two-equation k-ε and RNG k-ε models flow velocities with empirical modifications were led to poor results, especially the tangential components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…It can be observed that near the duct underflow position, 0.135 m, the profile resembles the parabolic behavior, with the concave side up, because the temperature of the conical wall is warmer than the center of the hydrocyclone and the fluid flow is downward in this region. At the axial positions 0.275 m and 0.412 m, the temperature profiles have approximately similar behavior, because the areas of recirculation and reverse flow present in this region and this is consistent with the literature [1,11,15].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…It can be observed that near the duct underflow position, 0.135 m, the profile resembles the parabolic behavior, with the concave side up, because the temperature of the conical wall is warmer than the center of the hydrocyclone and the fluid flow is downward in this region. At the axial positions 0.275 m and 0.412 m, the temperature profiles have approximately similar behavior, because the areas of recirculation and reverse flow present in this region and this is consistent with the literature [1,11,15].…”
Section: Resultssupporting
confidence: 79%
“…where Q α denotes heat transfer at the interface, from one phase to another phase, given by (10,11,12).…”
Section: Equation Of Momentum Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover the flow is unsteady due to the instability of the precessing vortex core. Hydrocyclone flows still present a challenge for CFD modelling due to the mentioned reasons [1][2][3][4][5][6][7][8][9][10][11][12]. It is worth noting that many features of the hydrocyclone flows are very similar to behaviour of cavitating vortex rope in draft tubes of hydraulic turbines, see [13].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computational technology, numerical simulations are becoming ever more important to investigate various flow phenomena. Many case studies have applied computational fluid dynamics (CFD) to these problems (Narasimha, Brennan, & Holtham, 2007;Stamou, Katsiris, Politis, & Schaelin, 2008;Wang, Reitz, Pera, Wang, & Wang, 2013). For studies of swimming fish, numerical studies have also provided insightful results, some of which may be difficult to obtain experimentally.…”
Section: Introductionmentioning
confidence: 99%